Predation Risk, and Not Shelter or Food Availability, as the Main Determinant of Reproduction Investment in Island Lizards - Johannes Foufopoulos; Yilun Zhao; Kinsey M. Brock; Panayiotis Pafilis; Efstratios D. Valakos (Animals, 2023)
Reproductive investment, including the number of offspring produced, is one of the fundamental characteristics of a species. It is particularly important for island vertebrates, which face a disproportionate number of threats to their survival, because it predicts, among other things, a species’ resilience to environmental disruption. Taxa producing more offspring recover more quickly from environmental perturbations and survive environmental change better. However, ecologists do not understand which primary drivers shape a species’ reproductive investment well. Here, we compare the reproductive efforts of 14 island populations of the Aegean Wall Lizard (Podarcis erhardii), which lives across widely diverging environmental conditions. We test three hypotheses, namely that reproductive investment (measured as clutch size, clutch volume) is (1) positively associated with predation risk [‘Predation Risk Hypothesis’]; (2) positively associated with the presence of reliable vegetation cover that provides shelter [‘Gravid Female Protection Hypothesis’]; and (3) limited by (and hence positively correlated with) food availability [‘Food Limitation Hypothesis’]. Although field data are somewhat consistent with all three hypotheses, statistical analyses provide strong support for the Predation Risk Hypothesis. The results not only shed light on which fundamental forces shape reproductive investment in island vertebrates, but can also help shape conservation priorities.